DIVERSI TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DALAM SISTEM PERADILAN PIDANA ANAK - Apshari Pinatih, I G. A. A.; Rai Setiabudi, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 01, Maret 2014, 2014)
In this paper with titled “Diversion Against The Children Who Faced the Law in The Juvenile Justice System"contains issues about regulations of disversion against the children who faced the law in the juvenile justice system and what is the purpose of applying diversion in the juvenile justice system. The method used is the method of normative legal by research with statute approach and the conceptual approach, while legal materials collection techniques using literature study which was materials collected will be analyzed qualitatively. The results at the momen is that the children who faced the law shall be pursued in the process of settlement outside the court lines through diversion based restorative justice approach. The conclusion that the diversion for the children in conflict with the law has stipulated in Law No. 11 of 2012 on the Juvenile Justice System has replaced Law No. 3 of 1997 on The Juvenile Justice, while implementation of diversion goal is to avoid and keep children out of the judicial process so as to avoid stigmatitasi against the children who faced the law and the children are expected to return to normal social environment.
Keywords: Diversion, Juvenile Justice System